Analisis Penggunaan Transaksi E-Wallet dalam Persfektif Ekonomi Syariah - Fatimah, Tita Siti; Aziz, Abdul; Sudrajat, Anton (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of financial technology in Indonesia has driven a major transformation in the payment system, one of which is through digital wallets or e-wallets. Data from the Financial Services Authority shows that the payment sector dominates the fintech industry, and e-wallets have become the fastest-growing transaction method. The popularity of e-wallets is inseparable from the convenience, efficiency, and speed they offer, so people are increasingly accustomed to conducting cashless transactions. However, behind this convenience lies the risk of personal data security that is vulnerable to misuse, so it is necessary to further study its compliance with Islamic muamalah principles. This research uses a literature study method with an interdisciplinary approach that combines the perspectives of Islamic economics and financial technology. The study results show that e-wallets are permissible in Islam as long as they do not contain elements of riba, gharar, maysir, and israf, and use valid contracts such as wadi’ah, qardh, ijarah, and wakalah. DSN-MUI Fatwas No. 116/2017 and No. 166/2017 serve as the legal basis that confirms the validity of sharia-compliant electronic money. Nevertheless, the phenomenon of excessive promotions such as cashback and discounts can encourage consumptive behavior that contradicts the principle of moderation (wasathiyah). Therefore, the use of e-wallets must be done wisely so that it remains aligned with the maqasid al-shari‘ah, namely maintaining justice, trustworthiness, transparency, and asset protection.